2008
DOI: 10.1093/cvr/cvn312
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of prostaglandin EP3 receptors activates calcineurin and promotes hypertrophy in the murine heart

Abstract: EP(3)-receptor-mediated signalling results in a significant anti-ischaemic action and activation of the pro-hypertrophic calcineurin signalling pathway, suggesting the involvement of the EP(3) subtype in both PGE(2)-mediated cardioprotection as well as cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Vital and colleagues 11 reported a case of a peripartum heart failure while another case showed that sulprostone caused coronary spasm, bradycardia, and subsequent asystole 12 . In EP3 over-expressing mice, LV ejection fraction was severely decreased in transgenic hearts while the relative LV mass was significantly increased 13 . Using isolated rat atria, Wolkowicz et al 14 also reported that an EP1 agonist increased contractile force that was sensitive to Rho kinase inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Vital and colleagues 11 reported a case of a peripartum heart failure while another case showed that sulprostone caused coronary spasm, bradycardia, and subsequent asystole 12 . In EP3 over-expressing mice, LV ejection fraction was severely decreased in transgenic hearts while the relative LV mass was significantly increased 13 . Using isolated rat atria, Wolkowicz et al 14 also reported that an EP1 agonist increased contractile force that was sensitive to Rho kinase inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, few studies on prostanoid receptor overexpression have been reported. In transgenic mice with cardiospecific EP 3 receptor overexpression, increased calcineurin and NFAT activity with cardiac hypertrophy were found (Meyer-Kirchrath et al, 2009).…”
Section: Distribution and Biological Functionsmentioning
confidence: 99%
“…Thereby, the cell specific role of EP4 receptor in cardiac remodeling is further required. With regard to EP3, although several reports suggested a cardioprotective effect of EP3 agonists against ischemia/reperfusion injury in rodents and pigs [7678], others demonstrated that overexpression of EP3 might activate calcineurin and promote hypertrophy after ischemia reperfusion [79]. These results suggest a dual involvement of the EP3 subtype in both cardioprotection and hypertrophy, which might be attributable to the expression diversity of EP3 isoforms in heart tissue.…”
Section: Ep Receptors and Myocardial Remodelingmentioning
confidence: 99%